2018
DOI: 10.3233/wor-182749
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and its related factors among dentists: A cross-sectional study

Abstract: Higher professional satisfaction was observed in the group of younger doctors working in the private sector in large cities. Women reported satisfaction more often than men. The external environment had no impact on professional satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
1
17
3
3
Order By: Relevance
“…Comparisons of the result of the present study with other studies revealed that the overall satisfaction scores of this study were low. The satisfaction scores in the present study were lower than that of studies conducted among dentists in China,[7] Poland,[14] South Korea (score of 3.2 out of 5),[11] Lithuania (score of 4.06 out of 5),[6] and India. [15] Furthermore, the mean scores of satisfaction among dental assistants reported in this study were lower than that reported earlier in Saudi Arabia by Aljazairy et al .…”
Section: Discussioncontrasting
confidence: 89%
“…Comparisons of the result of the present study with other studies revealed that the overall satisfaction scores of this study were low. The satisfaction scores in the present study were lower than that of studies conducted among dentists in China,[7] Poland,[14] South Korea (score of 3.2 out of 5),[11] Lithuania (score of 4.06 out of 5),[6] and India. [15] Furthermore, the mean scores of satisfaction among dental assistants reported in this study were lower than that reported earlier in Saudi Arabia by Aljazairy et al .…”
Section: Discussioncontrasting
confidence: 89%
“…This is in accordance with a study conducted by Kobza J et al and Pandita V et al where the dentists where reasonably satisfied with their jobs. 2,6 No significant differences were observed between males and females in the current study with regards to job performance, satisfaction and occupational stress. This finding is in accordance with a study in Yemen where no statistical differences were reported in stress among male and female dentists.…”
Section: Discussioncontrasting
confidence: 61%
“…There are many dimensions in dentistry that can lead to satisfaction or dissatisfaction and can even affect the performance and lead to increase in stress among dental practitioners. 2 Increased temperature can be one such factor. The present study was done to assess the effect of temperature on job performance, satisfaction and occupational stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The structure of dental care in Poland has a specific organization. [2] Most facilities are small or even 1-person dental offices. The dental office staff usually includes a dental assistant or hygienist; only in larger dental offices there is a medical secretary.…”
Section: Introductionmentioning
confidence: 99%